Domestic and Foreign Banks in Germany: Do They Differ? - Claudia M. Buch; Stefan M. Golder (Kiel Institute of World Economics (IfW), 2000)
The German banking market is notorious for its low degree of market penetration by foreign financial institutions, suggesting that markets serviced by domestic and foreign banks are segmented. This paper employs a number of tests to determine whether activities of domestic and foreign banks are related. Using data for the years 1986-1999, we fail to find evidence for similarities in the activities of domestic and foreign banks. This holds across the two types of domestic banks (large and savings banks) and across four different activities (loans and deposits of banks and non-banks) considered.
Keywords: G32; G24; G21; G15; 330; integration of banking markets; cointegration analysis; Bank; Internationale Bank; Vergleich; Deutschland